Carbonaceous Spheres – Versatile Intermediaries for Metal Oxide Spherical Structure Synthesis. Issue 6 (17th January 2014) - Patrinoiu, Greta; Calderon‐Moreno, Jose Maria; Somacescu, Simona; Spataru, Nicolae; Musuc, Adina M.; Ene, Ramona; Birjega, Ruxandra; Carp, Oana
Abstract: A facile, versatile, genuine green route that uses starch‐derived carbonaceous spheres as the templates and carbon source for tailor‐made ZnO spherical structures is described. A simple adjustment of the thermal treatment permits the generation of either ZnO/C solid microporous spheres or ZnO hollow spheres, the later with controlled diameter and shell morphology. The spherical structures demonstrate good photocatalytic activity for the visible light degradation of methylene blue. Furthermore, ZnO/C has promising electrochemical capacitor applications and good electrochemical and mechanical stability. Abstract : A versatile and green route that uses starch‐derived carbonaceous spheres as the templates and carbon source for tailor‐made ZnO spherical structures is described. The simple adjustment of the thermal treatment permits the generation of either ZnO/C microporous solid spheres or ZnO hollow spheres, the later with controlled diameter and shell morphology.